Centralization and the success of ERP implementation. Issue 5 (12th September 2016) - Nandi, Madhavi Latha; Kumar, Ajith
Abstract : Purpose: Centralization, which indicates distribution of decision-making power in organizations, is well-discussed in innovation literature as one of the influencing factors of innovation implementation. Motivated by a gap in enterprise resource planning (ERP) research, the purpose of this paper is to investigate the influence of centralization on the success of ERP implementation. Design/methodology/approach: Centralization is characterized twofold: policy-related centralization (PRC) and work-related centralization (WRC). ERP implementation success is captured in terms of user acceptance and the use of the ERP system. Using organizational innovation theory, six hypotheses relating centralization, ERP implementation success, and organization size are built and tested using data gathered from 51 Indian organizations that implemented ERP. The data are analyzed using partial least squares-structural equation modeling. Findings: User acceptance is significantly inhibited by PRC. WRC has a negative influence on use. The negative influence of PRC on acceptance is more pronounced in the case of larger organizations. On the whole, a decentralized set-up is favorable to ERP implementation success. Originality/value: The study highlights the impact of a centralized management structure on success of ERP implementation and in doing so, it demarcates the varied influence of two types of centralization. It contributes to the scarce research on ERP implementation using the strong theoretical basis of organizational innovation. The findings highlight the implications of centralization to the implementation outcomes, for organizations embarking upon ERP.